The influence of the East philosophy and the works of V. Solovyov on the work of M. Orest (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article devoted to the problem of influence of the philosophy of East and works of V.Solovjov in the poetry of M.Orest. Ideas about connection between the nature and people’s life, the victory of good in the fight between good and evil, respon-sibility of human, unity of humanity, undying of soul, transformation shows in analysis of poetry. The author used images of nature, in particular trees, spring as the season of rebirth, city as the plase of good and evil. The special attention M.Orest devoted to the question of moral perfection of humanity.
Keywords: morals; nature; person